2017
DOI: 10.9767/bcrec.12.3.592.452-459
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance for Hydrocarbon Production from Syngas on the Promoted Co-Based Hybrid Catalysts; Influence of Pt Contents

Abstract: Fischer-Tropsch synthesis (FTS) reaction from syngas was investigated on the Pt-promoted cobaltbased hybrid catalysts prepared by co-precipitation method in a slurry of ZSM-5 (Si/Al=25). The hybrid catalysts were compared with each other for the different content of Pt as a promoter and are characterized using BET, XRD, H2-TPR and NH3-TPD. Their physicochemical properties were correlated with the activity and selectivity of the catalysts. As results, all hybrid catalysts show the C5-C9 yield (%) higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Even strongly acidic sites showed no clear difference when the promoter was varied; however, the selectivity of C5-C9 was improved because of the strength of the weak acid points. Kang et al [120] reported the optimal Pt content is 0.3 wt%. They reported that, when the Pt content was increased, the C10+ selectivity increased.…”
Section: Zsm Supported Co-based Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Even strongly acidic sites showed no clear difference when the promoter was varied; however, the selectivity of C5-C9 was improved because of the strength of the weak acid points. Kang et al [120] reported the optimal Pt content is 0.3 wt%. They reported that, when the Pt content was increased, the C10+ selectivity increased.…”
Section: Zsm Supported Co-based Catalystmentioning
confidence: 99%
“…Cho et al [122] investigated the FTS reaction and the structural characteristics of Fe2O3 catalysts as functions of the pore size of mesoporous KIT-6. The pore size was changed to ~0.7 nm (M7), ~5 nm (B5), 4 nm and 3.6 nm (B4), etc., and KFe/KIT-6 (B5) was used as a promoter Kang et al [120] reported the optimal Pt content is 0.3 wt%. They reported that, when the Pt content was increased, the C 10 + selectivity increased.…”
Section: Kit-6 Supported Catalystsmentioning
confidence: 99%